Towards regional scientific integration in Africa? Evidence from co-publications - (:unkn) unknown (My University, 2023)
Regional scientific integration is a critical pathway for the development of an integrated African research area and knowledge-based society. On the African continent, progress in scientific production and integration has remained limited, mostly led by a global or international agenda, and bound to a few top publishing nations. The high-level policy commitments and the accumulated policies and strategies developed and pursued under the various intertwined sub-regional economic groupings have, to date, only diversely contributed to policy alignment and coordination in the area of science, technology, and innovation (STI) across Africa. In this context, this paper provides a first and hence original assessment of the role of region-specific factors in shaping scientific collaboration on the continent. For this purpose, our study builds upon the proximity approach to analyse the determinants of scientific collaboration between African countries, using co-publications data from Thomson Reuters' Web of Science database as a proxy of such collaboration. Our results suggest that the majority of African regional economic communities (RECs) have not yet had a significant effect on scientific co-publication. Nevertheless, some important region-specific factors do seem to be at play, such as a shared ethnical language, membership in the African and Malagasy Council for Higher Education (CAMES), and the presence of a common European partner as a third partner in co-publication. Existing policies aimed at the development of an Africa-wide research area should aim to leverage existing and emerging regional excellence networks and novel coordination models to accelerate the process of scientific integration in Africa.
Keywords: African Research